Isolation of digital dermatitis treponemes from cattle hock skin lesions. Issue 2 (21st January 2016) - Clegg, Simon R.; Bell, Jennifer; Ainsworth, Stuart; Blowey, Roger W.; Bell, Nick J.; Carter, Stuart D.; Evans, Nicholas J.
Abstract : Background: Bovine hock lesions present a serious welfare and production issue on dairy farms worldwide. Current theories suggest that trauma is an important factor in the formation of hock lesions, although infection may also play a role in increasing their severity and duration. Hypothesis: Digital dermatitis (DD) lesions in dairy cows are strongly associated with specific treponeme bacteria which are opportunistic invaders of other skin regions. Hock lesions were tested to ascertain if they too contained treponemes. Animals: Swab and tissue samples were taken from hock lesions from two farms in South West England. Methods: Hock lesions were classified into two categories: open lesions, which were often bleeding and ulcerated, or were encrusted; and closed lesions, which were classified as hair loss with no skin breakage. PCR assays and bacterial isolation were used to detect treponemes in hock lesions. Results: All three phylogroups of digital dermatitis treponemes were detectable and isolated from open hock lesions only, with closed lesions showing no evidence of treponeme infection, either by PCR or bacterial culture. When analysed by 16S rRNA gene sequencing, the cultured treponeme DNA showed complete homology or was very similar to that found in foot lesions. Additionally, skin swabs from near the open hock wounds were also positive by PCR assay and isolation for the DD treponemes. Conclusions and clinical importance: Identification of the contribution of these infectious agents will allow for more optimal treatments to be developed that reduce the prevalence and healing times of both hock and DD lesions. Abstract : Background – Bovine hock lesions present a serious welfare and production issue on dairy farms worldwide. Current theories suggest that trauma is an important factor in the formation of hock lesions, although infection may also play a role in increasing their severity and duration.Hypothesis – Digital dermatitis (DD) lesions in dairy cows are strongly associated with specific treponeme bacteria which are opportunistic invaders of other skin. Hock lesions were tested to ascertain if they, too, contained treponemes.Conclusions and clinical importance – Identification of the contribution of these infectious agents will allow for more optimal treatments to be developed that reduce the prevalence and healing times of both hock and DD lesions.